Effective awk programming - Robbins, Arnold (O'Reilly, 2001)
Effective awk Programming,3rd Edition, focuses entirely onawk, exploring it in the greatest depth of the three awk titles we carry. It's an excellent companion piece to the more broadly focused second edition. This book provides complete coverage of the gawk 3.1 language as well as the most up-to-date coverage of the POSIX standard forawk available anywhere. Author Arnold Robbins clearly distinguishes standard awk features from GNU awk(gawk)-specific features, shines light into many of the "dark corners" of the language (areas to watch out for when programming), and devotes two full ch
Includes indexes. - Print version record
Keywords: AWK (Computer program language); AWK (Langage de programmation); COMPUTERS; Programming Languages; C♯; COMPUTERS; Programming Languages; Java; COMPUTERS; Programming Languages; Pascal